Strategi Pengembangan Inkubator Bisnis Dalam Pendampingan Bisnis Usaha Mikro, Kecil, dan Menengah (UMKM): The Development Strategy of Business Incubator in Mentoring Micro, Small and Medium Enterprise (MSME) Business - Sitorus, Gloria Febriani; Machfud; Anggraeni, Elisa (School of Business, Bogor Agricultural University (SB-IPB), 2023)
Micro, Small and Medium Enterprises are one of the business actors in Indonesia that have considerable potential in supporting the national economy. Business incubators are one of the parties that can play a role in assisting the growth and development of micro, small and medium enterprises, but in practice business incubators face various limitations related to human resources, capital, facilities, coaching, technology, market potential and regulations. The influence of these limitations has an impact on the performance of mentoring or coaching, so it is necessary for business incubators to develop their mentoring programmes to be able to provide assistance in accordance with the needs needed by the current fostered tenants, so as to improve the business performance. This research aims to formulate an appropriate development strategy for the IPB Business Incubator by analysing the internal and external environment of the incubator. The method in this research uses the analysis of Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT analysis (Strengths-Weaknesses-Opportunities-Threats), and using Quantitative Strategic Planning Matrix (QSPM). The results showed that three strategies were recommended for the development of IPB's Business Incubator, namely developing an online marketing platform that can help market tenant products online, developing incubation programmes that can improve tenant competitiveness, and building cooperation with many parties both nationally and internationally. Keywords: business incubator, IFE matrix, EFE matrix, SWOT analysis, QSPM analysis